2012
DOI: 10.1515/cclm.2011.815
|View full text |Cite
|
Sign up to set email alerts
|

Faecal haemoglobin concentrations by gender and age: implications for population-based screening for colorectal cancer

Abstract: Faecal haemoglobin concentrations vary with gender and age. More tailored strategies are needed in screening programmes. Faecal haemoglobin concentration could be included in individual risk assessment scores. These data should assist in screening programme design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 18 publications
9
95
3
Order By: Relevance
“…88,140 Further, a recent study conducted in Scotland found that faecal Hb concentrations also increased with increasing levels of deprivation (measured using the Scottish Index of Multiple Deprivation) and that this trend remained after controlling for age and sex. 141 Thus, at any cut-off concentration, more men, more older people and more people in high deprivation groups are likely to have a positive result on faecal immunochemical testing.…”
Section: Clinical Effectivenessmentioning
confidence: 99%
“…88,140 Further, a recent study conducted in Scotland found that faecal Hb concentrations also increased with increasing levels of deprivation (measured using the Scottish Index of Multiple Deprivation) and that this trend remained after controlling for age and sex. 141 Thus, at any cut-off concentration, more men, more older people and more people in high deprivation groups are likely to have a positive result on faecal immunochemical testing.…”
Section: Clinical Effectivenessmentioning
confidence: 99%
“…Would readily available data such as age and sex, which have been shown to affect f-Hb (7,8) be usefully incorporated in a risk-based screening algorithm as suggested a number of times (14,17) and already shown to be potentially useful in use of f-Hb in the assessment of patients presenting with symptoms of CRC (18). This would be both simple and inexpensive but, as suggested, further research is necessary to determine the benefits of more complex algorithms incorporating variables other than f-Hb (14).…”
Section: F-hb Concentrations Below the Programme Applied Cut-offmentioning
confidence: 99%
“…Following review, 19 studies were eligible for inclusion in the review and meta-analysis (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). A flow chart of the search strategy results is provided in Fig.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%